2012
DOI: 10.1117/12.908642
|View full text |Cite
|
Sign up to set email alerts
|

Combined photoacoustic and ultrasonic diagnosis of early bone loss and density variations

Abstract: Over the past two decades, osteoporosis has been recognized among the most serious public health problems. Fortunately with the growing awareness of osteoporosis, new treatments have been developed for the prevention of fracture. At the same time, there is a rapid improvement in diagnostic methods. In this study biomedical photoacoustics (PA) is applied to the analysis of bone mineral concentration. The PA signal depends on optical as well as mechanical properties of the object and therefore has the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…28 Recently, measurements of photoacoustic (PA) backpropagation from bones were reported for the first time. 30,31 Since PA is sensitive to the optical properties of tissue, it can detect composition variation and as such it can provide complementary information to US backscattering measurements. In our previous studies, we showed the sensitivity of PA with changes in minerals and organic phases of bone.…”
Section: Introductionmentioning
confidence: 99%
“…28 Recently, measurements of photoacoustic (PA) backpropagation from bones were reported for the first time. 30,31 Since PA is sensitive to the optical properties of tissue, it can detect composition variation and as such it can provide complementary information to US backscattering measurements. In our previous studies, we showed the sensitivity of PA with changes in minerals and organic phases of bone.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has examined the possibility of PA to the evaluation of bone mineral concentration and microstructure [12][13][14]. Although the findings from this study are mostly qualitative, it demonstrates potential advantages of PA based bone evaluation over conventional US based technologies.…”
Section: Introductionmentioning
confidence: 80%
“…Although the findings from this study are mostly qualitative, it demonstrates potential advantages of PA based bone evaluation over conventional US based technologies. Since the light-induced pressure waves are generated instantaneously from different layers, PA measurement from a bone can focus on the trabecular part as the region of interest (ROI) without being affected by the cortical part [12]. In this work, with an ultimate goal of establishing a quantitative photoacoustic (QPA) platform for assessment of bone health, we investigated the performance of several techniques, including photoacoustic imaging (PAI), thermal photoacoustic measurement (TPAM), photoacoustic spectral analysis (PASA), on ex vivo bone specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Our group introduced PA diagnostics for studies of bone density changes. In our previous work, 37 we showed that the PA signal is sensitive to large changes in the trabecular bone structure. We also showed that "coherent structure backscattering" similar to US 38 can be detected with PA at frequencies higher than 1 MHz.…”
Section: Introductionmentioning
confidence: 90%